Characteristics of sprint performance in college football players - Brechue, W. F.; Mayhew, J. L; Piper, F. C. (The Journal of Strength and Conditioning Research, 2010)
To investigate sprinting strategy, acceleration and velocity patterns were determined in college football players (n = 61) during performance of a 9.1-, 36.6-, and 54.9-m sprints. Acceleration and velocity were determined at 9.1-m intervals during each sprint. Lower-body strength and power were evaluated by 1 repetition maximum (1-RM) squat, power clean, jerk, vertical jump, standing long jump, and standing triple jump. Sprint times averaged 1.78 +/- 0.11 seconds (9.1 m), 5.18 +/- 0.35 seconds (36.6 m), and 7.40 +/- 0.53 seconds. Acceleration peaked at 9.1 m (2.96 +/- 0.44 m[middle dot]s-2), was held constant at 18.3 m (3.55 +/- 0.0.94 m/s), and was negative at 27.4 m (-1.02 +/- 0.72 m/s). Velocity peaked at 18.3 m (8.38 +/- 0.65 m/s) and decreased slightly, but significantly at 27.4 m (7.55 +/- 0.66 m/s), associated with the negative acceleration. Measures of lower-body strength were significantly related to acceleration, velocity, and sprint performance only when corrected for body mass. Lower-body strength/BM and power correlated highest with 36.6-m time (rs = -0.55 to -0.80) and with acceleration (strength r = 0.67-0.49; power r = 0.73-0.81) and velocity (strength r = 0.68-0.53; power r = 0.74-0.82) at 9.1 m. Sprint times and strength per body mass were significantly lower in lineman compared with linebackers-tight ends and backs. The acceleration and velocity patterns were the same for each position group, and differences in sprint time were determined by the magnitude of acceleration and velocity at 9.1 and 18.3 m. Sprint performance in football players is determined by a rapid increase in acceleration (through 18.3 m) and a high velocity maintained throughout the sprint and is independent of position played. The best sprint performances (independent of sprint distance) appear to be related to the highest initial acceleration (through 18.3 m) and highest attained and maintained velocity. Strength relative to body mass and power appears to impact initial acceleration and velocity (through 18.3 m) in contribution to sprint performance.